In-situ observations of static recrystallization and texture formation in a cold-rolled CoCrFeMnNi high entropy alloy. (1st July 2022) - Guo, Baoqi; Ray, Ranjit K.; Yoshida, Shuhei; Bai, Yu; Tsuji, Nobuhiro
Abstract: Static recrystallization and texture development in a CoCrFeMnNi high entropy alloy cold-rolled to various strains and annealed were studied. Microstructural and crystallographic evolution was recorded by identical area observations using quasi in-situ electron backscatter diffraction (EBSD). The deformation texture was preserved after recrystallization, but the texture was weakened at this stage. Shear bands served as the preferential nucleation sites for recrystallization. Thin foils of the deformed alloy were in-situ observed during heating in a transmission electron microscope (TEM). It was observed that subgrains formed from deformed microstructures by dislocation rearrangement and annihilation. The subgrains coarsened by boundary migration and coalescence. These enlarged subgrains were the viable nuclei for the recrystallized grains. Graphical abstract: Image, graphical abstract